Heterozygous frameshift mutation in keratin 5 in a family with Galli–Galli disease. (1st June 2014) - Reisenauer, A.K.; Wordingham, S.V.; York, J.; Kokkonen, E.W.J.; Mclean, W.H.I.; Wilson, N.J.; Smith, F.J.D.
Summary: Background: Reticulate pigmentary disorders include the rare autosomal dominant Galli–Galli disease (GGD) and Dowling–Degos disease (DDD). Clinical diagnosis between some of the subtypes can be difficult due to a degree of overlap between clinical features, therefore analysis at the molecular level may be necessary to confirm the diagnosis. Objectives: To identify the underlying genetic defect in a 48‐year‐old Asian‐American woman with a clinical diagnosis of GGD. Methods: Histological analysis was performed on a skin biopsy using haematoxylin–eosin staining. KRT5 (the gene encoding keratin 5) was amplified from genomic DNA and directly sequenced. Results: The patient had a history of pruritus and hyperpigmented erythematous macules and thin papules along the flexor surfaces of her arms, her upper back and neck, axillae and inframammary areas. Hypopigmented macules were seen among the hyperpigmentation. A heterozygous 1‐bp insertion mutation in KRT5 (c.38dupG; p.Ser14GlnfsTer3) was identified in the proband. This mutation occurs within the head domain of the keratin 5 protein leading to a frameshift and premature stop codon. Conclusions: From the histological findings and mutation analysis the individual was identified as having GGD due to haploinsufficiency of keratin 5.